(untitled) (Research, Society and Development, 2021)
The aim of this study was to analyze the quality of sleep of residents of two multiprofessional health residency programs and to identify which residency program has the highest frequency of sleep-related disorders. This research is characterized as an exploratory, descriptive and quantitative cross-sectional study. This is a probabilistic sample, in which all participants had a greater than zero chance to respond. For data collection, a sociodemographic questionnaire prepared by the authors was used, containing personal data such as age, sex, marital status, professional category and the residence of which it was part. The second questionnaire was the Pittsburgh Sleep Quality Index (IQSP), which was validated for Brazilian Portuguese in 2008. The overall IQSP score was high. The perception of sleep quality was classified by the residents as very bad, 90.15% of the sample. Investment in the health and well-being of this population should also aim to improve professional and educational qualifications, with an impact on the quality of services provided to users of the Unified Health System.